1986
DOI: 10.1037/0278-6133.5.5.439
|View full text |Cite
|
Sign up to set email alerts
|

Perceived stress and diabetes control in adolescents.

Abstract: Studies of diabetes control have traditionally focused on patients' regulation of insulin, diet, and exercise. Although psychosocial stress may also influence blood glucose, researchers have infrequently accounted for the three primary physiological factors when estimating the effects of stress. In addition, few investigators have considered the influence of everyday minor stressors on health outcome. The Tennessee Camp for Diabetic Children provided an opportunity to monitor insulin administration, dietary in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

1989
1989
2005
2005

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(35 citation statements)
references
References 23 publications
1
34
0
Order By: Relevance
“…One study (9) assessed IOR between an observer and an additional observer who only conducted IOR observations. Only 10 (5,6,19,20,23,24,26,27,30,31) of the remaining 22 studies mentioned assessment of IOR during data collection and provided methodologic information and/or results for IOR; three of these studies (5,6,20) were conducted by our group and are discussed further in this article.…”
Section: During Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study (9) assessed IOR between an observer and an additional observer who only conducted IOR observations. Only 10 (5,6,19,20,23,24,26,27,30,31) of the remaining 22 studies mentioned assessment of IOR during data collection and provided methodologic information and/or results for IOR; three of these studies (5,6,20) were conducted by our group and are discussed further in this article.…”
Section: During Data Collectionmentioning
confidence: 99%
“…For direct observation of meals, observers typically watch subjects throughout a defined period (eg, school lunch) and take notes on the subjects' eating behaviors regarding items and amounts consumed, traded (received/given away), and/or spilled. Examples of 26 studies in which direct observation has been used include studies to validate dietary recalls (5,6,(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22), food frequency questionnaires (11,23), and food/diet records (11,24) as well as studies to assess dietary intake of individuals (25)(26)(27)(28)(29)(30)(31) and to evaluate nutrition education interventions (31).…”
mentioning
confidence: 99%
“…Despite the well-defined pathophysiology of intercurrent illness and surgery on carbohydrate metabolism that may lead to hyperglycemia, many studies have also demonstrated that stress may result in diminished glucose values. [7][8][9][10][11][12][13][14][15][16][17][18][19] This reduction in glucose seen in times of stress is frequently attributed to insufficient administration of exogenous glucose.…”
Section: Diabetes Is the Secondary Not Primary Problemmentioning
confidence: 99%
“…10 Other studies have failed to link Staphylococcal carriage to insulin injection but have shown a high carriage rate for both insulin-and noninsulin-using diabetic patients. 11 Some investigators have suggested that individuals with diabetes have a higher incidence of both Staphylococcal bacteremia and excess mortality. 12 However, those studies remain inconclusive.…”
mentioning
confidence: 99%
“…On the contrary, previous hardiness research has been based heavily on retrospective studies and this is thought to weaken the interpretation of hardiness as a stress resistance resource. If hardiness is to be interpreted as a stress buffer, it must be shown that stress adversely affects health and that hardiness mitigates these negative changes ( Hanson and Pichert, 1986). In there study, hardiness did not work through stress to affect illness cause; stress itself had a weak direct effect.…”
Section: Hardinessmentioning
confidence: 81%